US Extremism on Telegram: fueling Disinformation, Conspiracy Theories, and Accelerationism - Walther, Samantha (Perspectives on terrorism, 2021)
Several alternative social media platforms have emerged in response to perceptions that mainstream platforms are censoring traditional conservative ideologies. However, many of these alternative social media platforms have evolved to be outlets for hate speech and violent extremism. This study examines hate-based channels on Telegram from a US perspective. While Telegram has often been studied in relation to ISIS, less is known about its usage by US extremist users and movements. The authors used OSINT and observational methods on a sample of 125 Telegram channels containing hate speech and violent extremist content from far-right and far-left perspectives. The authors hypothesized that there would be a greater and growing presence of far-right activity compared to farleft activity due to current migration trends away from mainstream social media by the far-right. The authors also sought to observe the presence of disinformation campaigns, conspiracy theories, and accelerationism on Telegram. This study had four major findings: (1) the findings supported the hypothesis that more channels were host to farright dialogues, yet there were several far-left channels present, (2) 64.8% of the channels grew in size over a oneweek period, (3) 47 of the 125 channels were connected to well-known violent extremist movements or hate groups, and (4) QAnon and the COVID-19 pandemic were the most prominent sources of disinformation and conspiracy theories on Telegram. The findings of this study highlight that alternative social media platforms are a growing environment for a range of hateful ideologies and are aiding the spread of disinformation campaigns. This study concludes with a discussion on future strategies to combat the influence of the Internet on radicalization outcomes.